Vent distribution in the Quaternary Payún Matrú Volcanic Field, western Argentina: Its relation to tectonics and crustal structures - Hernando, Irene Raquel (2014)
The Payún Matrú Volcanic Field consists of two polygenetic and mostly trachytic volcanoes (Payún Matrú with a summit caldera and Payún Liso) along with around 220 scoria cones and basaltic lava flows. This volcanic field belongs to the Payenia Basaltic Province (33° 30′–38° S), a Quaternary Andean back-arc basaltic province of the Southern Volcanic Zone, in western Argentina. The vent density distribution of the Payún Matrú Volcanic Field is different from the other volcanic fields within Payenia. The Payún Matrú volcano and the scoria cones are distributed in an E–W oriented fringe about 15 km wide and 70 km long, with the Payún Matrú caldera in the middle of this fringe. The structural framework in which the volcanic field is located allows to infer that this vent density distribution is strongly conditioned by pre-existing crustal anisotropies. The volcanic field is located in a transfer zone related to Jurassic extensional structures of the Neuquén Basin, which were inverted also as a transfer zone during the Miocene compressive deformation that formed the Malargüe fold and thrust belt, and, in addition, it is located in the southern margin of a Neogene syn-orogenic basin. The analysis of vent center location and vent morphology is helpful to determine basaltic vent alignments within the Payún Matrú Volcanic Field and to infer the syn-eruptive stress field. This analysis shows that vent alignments are compatible with the present-day maximum horizontal stress, as measured by break-out of oil wells.